Valuing depression using the well-being valuation approach - Daniela Andrén (Örebro University School of Business, 2020)
The continuously dramatic increase of the number of people suffering from depression attracts an increasing demand for effective ways of preventing depression. Without the need for new interventions, there is also a continuous call for a more robust framework for economic evaluation of public interventions. Taking in account people's preferences for public goods is not straightforward to quantify, and therefore, without the importance of designing new technique for valuing nonmarket goods and services, it is equally important to use methods that are not yet established as traditional. One less used method to assess the cost of depression in monetary terms is the well-being valuation method or the life satisfaction approach, which requires answers to questions that are significantly less time demanding for the respondents than more traditional approaches to valuation. We added a well-being question to a contingent valuation web-survey that describes hypothetical interventions aimed to prevent depression and estimated that the loss in life satisfaction for individuals who directly and/or indirectly experienced depression varies between approximately 5000 and 17000 Euro per year.
Keywords: A12; D60; I31; 330; depression; subjective well-being; well-being valuation method (WVM); life satisfaction approach (LSA)